Choice and success of job search methods - Andrea Maria Weber; Helmut Mahringer (Institute for the Study of Labor (IZA), 2006)
Job seekers can influence the arrival rate of job offers by the choice of search effort and the search methods they use. In this paper we empirically investigate the contribution of the use of different search methods on the outcome of search. We use unique data on the search behavior of job seekers sampled from the inflow into employment during the year 1997 in Austria, which matches survey information with administrative records. We analyze the quality of job matches in terms of wages and job durations for employed and unemployed workers. Our main finding is that the public employment service specializes in the support of low quality workers. For these workers it is equal in efficiency to the other search channels.
Keywords: J20; J64; C31; 330; job search; search channels; selectivity bias; Erfolgsfaktor; Arbeitsvermittlung; Soziale Beziehungen; Schätzung; Österreich